If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + n + n = 3n + -1(6 + 5) Combine like terms: n + n = 2n -6 + 2n = 3n + -1(6 + 5) Combine like terms: 6 + 5 = 11 -6 + 2n = 3n + -1(11) Multiply -1 * 11 -6 + 2n = 3n + -11 Reorder the terms: -6 + 2n = -11 + 3n Solving -6 + 2n = -11 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -6 + 2n + -3n = -11 + 3n + -3n Combine like terms: 2n + -3n = -1n -6 + -1n = -11 + 3n + -3n Combine like terms: 3n + -3n = 0 -6 + -1n = -11 + 0 -6 + -1n = -11 Add '6' to each side of the equation. -6 + 6 + -1n = -11 + 6 Combine like terms: -6 + 6 = 0 0 + -1n = -11 + 6 -1n = -11 + 6 Combine like terms: -11 + 6 = -5 -1n = -5 Divide each side by '-1'. n = 5 Simplifying n = 5
| 7(3)+4y=8y-1(3) | | x+15=6x-20 | | -5z+7(2-3z)= | | -0.1x-0.4x-6=2 | | -4+-3=2+p | | 4(7x+8)= | | 5y-10+y+40=5y+30-1y | | 6z-22=8z+6 | | -6(n+5)+2n=-37-5n | | -3x-4-6x=86 | | 4x+x+10=-30 | | 4x+7=3+5x-9 | | 18+999999898989898989= | | 5x+13x=180 | | 7-1= | | (3x+5)(2x-7)= | | 28-5y=40-6y | | -5=v-12 | | 5+4x+3x=82 | | 7(w-8)-(2+3w)=3w | | 7x+17=4x+32 | | 4(x-5)-2(x-3)=2x-14 | | -8.3-6x-4.7-x=-6x-2.2 | | 4x+8=2y | | xy=60 | | 5+2x/3x-1x=3/2 | | 2x+2y=32 | | 6f^2-17f+12=0 | | X-(-30)=40 | | 3x^2y(2x^3+5xy-y^2)= | | 4x+3-7x=-9 | | 8-(3z-6)=8-4z |